Patients' Awareness of the Complications of Bisphosphonate Therapy - Meri Hristamyan; Ralista Raycheva; Veselka Hristamyan (University Library System, University of Pittsburgh, 2022)
INTRODUCTION: Bisphosphonate-associated osteonecrosis of the jaws (BAONJ) is a serious complication that has been reported predominantly in cancer patients treated with Bisphosphonate (BP). The level of knowledge of dental and medical practitioners, as well as patients, is crucial for its prevention. OBJECTIVES: To investigate patients' awareness of BAONJ in order to evaluate some problems of the prevention, prophylaxis and diagnosis.         MATERIALS AND METHODS: A prospective epidemiological study of 112 oncology patients diagnosed with Bisphosphonate-associated osteonecrosis of the jaw was conducted in the Clinic of maxillo-facial surgery of university multiprofile hospital for active treatment (UMHAT) "St. George", Plovdiv, Bulgaria, based on anamnesis, clinical examination, hospital documentation, and imaging studies. SPSS Statistics v.24 was used for statistical analysis, at a significance level p<0.05. RESULTS: Before initiation of therapy, only 17.86% of the patients were consulted by a medical practitioner about the risk of jaw complications associated with the use of Bisphosphonates, 9.82% knew about the need for regular dental check-ups after the initiation of therapy and 4.46% had a dental examination and oral sanation. By the time of diagnosis, 61.61% of the patients remained unaware, with the last dental manipulation being most often extraction (52.68%) and removable dentures (21.42%) considered risky by experts. Diagnosed by a general dental practitioner or oncologist were 6.74% of the respondents - the medical practitioners who usually monitor the condition of these patients. Over 2/3 of the patients were diagnosed at a more advanced stage (II/III). CONCLUSION: The lack of patient awareness leads to omissions and errors in their prophylaxis, and to the diagnosis of BAONJ at a more advanced stage.